Bipolar Disorder and Parkinson disease: a 123I-FP-CIT SPECT study - G. D’agostino; G. Cascino; A. M. Landolfi; R. Erro; P. Barone; P. Monteleone (European Psychiatry, 2023)
Introduction Bipolar Disorder (BD) has been suggested to be a risk factor for development of Parkinson Disease. Psychiatric drugs used as standard treatment of BD includes many drugs that are known to induce drug-induced parkinsonism (DIP). Objectives Clinical differentiation between PD and DIP is a clinical and scientific crucial result. It might be aided by functional neuroimaging of the dopaminergic nigrostriatal pathway. Methods Twenty consecutive BD patients with parkinsonism were clinically assessed and underwent 123I-ioflupane dopamine transporter SPECT. Imaging data of BD patients with pathological nigrostriatal pathway were further compared to a population of de-novo PD patients. Results Four BD patients had abnormal scans; they had higher putaminal binding ratio and putamen-to-caudate ratios than PD patients, despite similar motor symptom burden. Conclusions in our initial results, up to 20% of BD patients with parkinsonism might have an underlying dopaminergic deficit, which is higher than excepted in the general population. This evidences supports that BD represents a risk factor for subsequent development of neurodegenerative parkinsonism. Disclosure of Interest None Declared